Efficient biosynthesis of 3-hydroxypropionic acid from ethanol in metabolically engineered Escherichia coli. (November 2022) - Lu, Juefeng; Wang, Yuying; Xu, Mingcheng; Fei, Qiang; Gu, Yang; Luo, Yuanchan; Wu, Hui
Graphical abstract: The metabolic pathway for the 3-HP production from ethanol. Highlights: Potential techniques to utilize ethanol and CO2 to produce 3-hydroxypropionic acid. The engineered E. coli can efficiently utilize ethanol as the sole carbon source. The engineered E. coli produced 1.66 g/L 3-HP from ethanol in batch culture. The titer of 3-HP reached 13.17 g/L in the whole-cell biocatalysis system. Abstract: Engineering microbial cell factories to convert CO2 -based feedstock into chemicals and fuels provide a feasible carbon–neutral route for the third-generation biorefineries. Ethanol became one of the major products of syngas fermentation by engineered acetogens. The key building block chemical 3-hydroxypropionic acid (3-HP) can be synthesized from ethanol by the malonyl-CoA pathway with CO2 fixation. In this study, the effect of two ethanol consumption pathways on 3-HP synthesis were studied as well as the effect of TCA cycle, gluconeogenesis pathway, and transhydrogenase. And the 3-HP synthesis pathway was also optimized. The engineered strain synthesized 1.66 g/L of 3-HP with a yield of 0.24 g/g. Furthermore, the titer and the yield of 3-HP increased to 13.17 g/L and 0.57 g/g in the whole-cell biocatalysis system. This study indicated that ethanol as feedstock had the potential to synthesize 3-HP, which provided an alternative route for future biorefinery.